2009
DOI: 10.1080/17450390903020406
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of ruminal fermentation and methane production by dietary saponins and tannins from mangosteen peel and soapberry fruit

Abstract: Four fistulated Holstein Friesian heifers were used in a 4 × 4 Latin square design with a 2 × 2 factorial arrangement. The main factors were two roughage-to-concentrate ratios (R:C, 70:30 and 30:70) and two supplementation levels of soapberry fruit-mangosteen peel (SM) pellets (0 and 4% tannins-saponins of total diets). Rice straw was used as a roughage source. The diet was fed ad libitum as a total mixed ration. SM pellets contained crude tannins and saponins at 12.1 and 15.7% of DM, respectively. It was foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 76 publications
(75 citation statements)
references
References 35 publications
4
68
1
2
Order By: Relevance
“…There are reports indicating a decrease in methane production with the supplementation of plant containing condensed tannins and saponins (Poungchompu et al 2009;Wanapat et al 2014;Anantasook et al 2016;Gunun et al 2016). Supplementation of RPP at 16 mg reduced methane production in the present study.…”
Section: In Vitro Rumen Fermentation and Methane Productionmentioning
confidence: 51%
See 2 more Smart Citations
“…There are reports indicating a decrease in methane production with the supplementation of plant containing condensed tannins and saponins (Poungchompu et al 2009;Wanapat et al 2014;Anantasook et al 2016;Gunun et al 2016). Supplementation of RPP at 16 mg reduced methane production in the present study.…”
Section: In Vitro Rumen Fermentation and Methane Productionmentioning
confidence: 51%
“…A decrease in methane production by tannins and saponins in Samanea saman could be mediated through a direct effect on protozoa and methanogens (Anantasook et al 2015). Poungchompu et al (2009) reported that supplementation of mangosteen peel and soapberry fruit pellet containing tannins and saponins at 4% of DM intake resulted in a significant decrease in methane production and protozoa population, but without affecting the methanogens in dairy heifers. In the current study, the methane-inhibiting effects of condensed tannins and saponins in RPP were presumably a direct action against rumen microbes involved in methane formation including methanogens and protozoa.…”
Section: In Vitro Rumen Fermentation and Methane Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mangosteen peel, guava leaf, and siam neem leaf contained condensed tannins, which ranged from 11.4% to 16.8% (Ngamsaeng et al 2006). However, soap berry tree fruit and mangosteen peel have been shown to contain high concentrations of crude saponins (20.1% and 10.0%, respectively) (Ngamsaeng et al 2006;Poungchompu et al 2009;Pilajun and Wanapat 2011). Condensed tannins are found in a multitude of plants around the globe.…”
Section: Chemical Composition and Active Ingredientsmentioning
confidence: 97%
“…[72][73][74]. Furthermore, a recent research showed that protein in cassava chips can be enriched by yeast fermentation up to 47.5% crude protein, which can be used as a replacement for soybean meal [75].…”
Section: 6mentioning
confidence: 99%